Поделки из спичек: просто и увлекательно - Зайцева Анна Анатольевна (Азбука рукоделия, 2011)
Экземпляры: ф.13 (20131217) / Инвентарный номер: 45400 / Цена: 123.00 / Авт.знак: З-17 / ГРНТИ: 64.33 / ББК: 37.248